2013
DOI: 10.1111/ijpp.12041
|View full text |Cite
|
Sign up to set email alerts
|

Screening for major diseases in community pharmacies: a systematic review†

Abstract: Available evidence suggests that screening for some diseases in community pharmacies is feasible. More studies are needed to compare effectiveness and cost-effectiveness of pharmacy-based screening with screening by other providers. Strategies to improve screening participants' adherence to pharmacist advice also need to be explored. This systematic review will help to inform future studies wishing to develop community pharmacy-based screening interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 61 publications
7
79
0
Order By: Relevance
“…Users of pharmacy services generally display high levels of satisfaction 27 and encouragement to recommend services to others, through the use of promotional cards/leaflets could prove a useful strategy. Linking of services has been advocated by pharmacists 3,28 and is being explored in research studies 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Users of pharmacy services generally display high levels of satisfaction 27 and encouragement to recommend services to others, through the use of promotional cards/leaflets could prove a useful strategy. Linking of services has been advocated by pharmacists 3,28 and is being explored in research studies 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of screening services have been provided by community pharmacies for other chronic conditions internationally, our review found that little has been done in asthma. The systematic review conducted by Ayorinde et al 66. also identified a number of studies for screening of various chronic conditions like cardiovascular disease, musculoskeletal disease, diabetes, or osteoporosis, but very few for asthma 66…”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacists' role in the prevention and management of diseases such as asthma, CVD, diabetes, and hypertension is well established [1]. However, our literature search could not identify any study that used community pharmacies as a resource for early identification and prevention of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Given their training and accessibility, community pharmacists are well placed to play a key role in providing health promotion and screening services to the general population [1]. In Australia, pharmacists have successfully implemented, within their normal daily practice, many interventional programs such as for asthma management [2], home-based post discharge warfarin management [3], detecting and resolving drugrelated problems [4], and cardiovascular disease (CVD) risk screening [5].…”
Section: Introductionmentioning
confidence: 99%